Financial sustainability of small and medium enterprises: a bibliometric analysis/ Normaizatul Akma Saidi ... [et al.] - Saidi, Normaizatul Akma; Mohd Radzi, Naziatul Aziah; Mohd Ali, Ahmad Fahme; Ab Ghaffar, Siti Fatimah (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2022)
Financial sustainability is critical for small and Medium Enterprises (SMEs) to sustain their business operations in difficult times. The financial sustainability of SMEs is a fairly new phenomenon, so the literature is still in its infancy. The purpose of this study is to investigate the financial sustainability of SMEs. For this reason, this study will specifically focus on four pillars of financial sustainability, namely 1) financial and strategic planning, 2) income diversification, 3) sound administration and finances, and 4) own income generation. This article focuses on the documents published in the database Elsevier Scopus on the topic of financial sustainability. Although the topic of financial sustainability has now gained considerable prominence, to date there has been no holistic bibliometric analysis on this topic. This study, therefore, attempts to fill this research gap. The findings of the study help academics and practitioners navigate the literature on financial sustainability, provide a systematic basis for the development of the field, and point to promising avenues for further research.